Desenvolvimento de um dispositivo para estudo de esquiva inibitória - Reghelin, Felipe Ponsi (Universidade Federal do Pampa, 2012)
Memory can be defined as the retaining and recalling of information learned. Being a dy-namic process, it requires the activation of several systems to consolidate the information gained. Thus, studies on Inhibitory Avoidance is of paramount importance to a better under-standing of the learning behavior. This work presents the development of an apparatus for car-rying out studies on Inhibitory Avoidance. The work discusses the design and operation of a variable current source for testing in rats. It is also developed a study on the value of the elec-trical resistance of rat. The simulations of the proposed topology were conducted in Orcad Schematics and Proteus Software and its results are shown along the work. The choice of a topology using transistors was made due to the high voltage levels needed for the current source operation.
Keywords: Electrical engineering; Inhibitory avoidance; Rats; Electrical resistance; Engenharia elétrica; Esquiva inibitória; Ratos; Resistência elétrica; CNPQ::ENGENHARIAS::ENGENHARIA ELETRICA